Functional morphology of the male reproductive system of the white shrimp Litopenaeus schmitti (Burkenroad, 1936) (Crustacea, Penaeidea) compared to other Litopenaeus - Fransozo, V. [UNESP]; Fernandes, A. B.; López-Greco, L. S.; Zara, F. J. [UNESP]; Santos, D. C. [UNESP] (Taylor & Francis, 2016)
The male reproductive system of L. schmitti is described, including spermatozoon ultrastructure. The testis is composed of 8 to 14 lobules arranged as seminiferous tubules. The proximal vas deferens is short and filled with spermatozoa without spikes. The median vas deferens is larger than the other parts of the vas deferens and it shows two ducts separated by typhlosoles, the sperm and accessory ducts. The former is filled with sperm masses, while the accessory duct shows only secretions that are part of the spermatophore material. In this region, the spermatozoa have a spike, indicating the end of the spermatogenesis. The distal vas deferens is a short tube ending in the ampulla, composed of three parts. The spermatozoa have a round main body and an anterior spike associated with the acrosomal cap. The subacrosomal space has a centrosome-like structure above the nucleus. The features of the male reproductive system of L. schmitti share the pattern of penaeoidean shrimps with closed thelyca related to the median vas deferens and the ampulla. All the differences in spermatozoon morphology and vasa deferentia are discussed, and compared to other Litopenaeus species.
Keywords: Histology; Penaeini; Penaeoidea; reproductive trait; seminal fluid; spermatozoon ultrastructure